Choix linguistique et modernité islamique au Cameroun - Hamadou Adama (Revue des Mondes Musulmans et de la Méditerranée)
This paper discusses the interplay between Islam, Arabic and Fulfulde in Cameroon with regard to a dual relationship based on competition and cooperation. Language plays a predominant role in the relationship between the universality of the Islamic dogma and the contextualized interpretations of it. The exploration of the cross-currents of fulanization [Fulfuldization] of Arabic and Arabization of Fulfulde, the interference between the linguistic activism of Christian missions and Muslim militants and the relation between orality and writing shed light on the internal and external dynamics and on the modes of invention/reinvention of a certain modernity. The proponents of the Islamic tradition and the militants of modernity maintain a realistic relationship, translated at the linguistic level into mixing and mutual influences between Arabic and Fulfulde.